The Advocacy Coalition Framework Approach to Row House Policy in Tamansari, Bandung City - Rama Akbar Ramadhan (Jurnal Manajemen Pelayanan Publik, 2020)
Conflicts between Governance actors are rife in the era of democracy as it is today. The purpose of this study is to analyze the problems of land conflicts faced by the community against the Bandung City Government which is in a joint coalition with PT Sartonia Agung. Those two parties had a dispute over land rights in RW 11 Tamansari to control the basis of rights for housing and the construction of Row House. The struggle of each party in the struggle for land in RW 11 Tamansari was carried out through an advocacy process with both formal and informal approaches. The Advocacy Coalition Framework in this study was used as a knife for analyzing the phenomena that occurred. The research methods used in this study were qualitative research by standing on the interpretative paradigm. The data were collected by conducting observations, in-depth interviews, and documentation relating to the outline of the research. The findings obtained from this study indicated that there was a formation of strong coalition domination by the government through aggressive and repressive behavior that raised a conflict of interest in the row house construction policy in Tamansari Subdistrict, Bandung City, which was rejected by the Coalition of the Tamansari community that was formed. The series of advocacy carried out by the Tamansari community coalition had not produced results in favor of the coalition that urged a change in the policy.